Development of a Multi-Well Pairing System for Groundwater Heat Pump Systems - Hongkyo Kim; Yujin Nam; Sang mu Bae; Oun Jeoun (Energies, 2018)
Groundwater heat pump systems (GWHPs) can achieve higher coefficient of performance (COP) than air-source heat pump systems by using the relatively stable temperature of groundwater. Among GWHPs, multi-well systems have lower initial investment costs than conventional closed-loop geothermal systems, because they typically require installation of fewer boreholes for the same building load. However, the performance of GWHPs depends significantly on the groundwater properties, such as groundwater temperature, permeability and water quality. Moreover, pumping and injecting of groundwater during long-term operation may lead to problems such as overflow or clogging of the wells. In order to ensure reliable energy from ground sources, the development of sustainable operation methods for multi-well systems is essential for preventing overflow and well clogging. In this study, we have developed a pairing technology that connects the injection and supply wells through a spillway. This pairing technology can be used to control groundwater levels in wells and can be sustainably operated. To accurately estimate the performance of a multi-well system with the proposed pairing technology, the heating and cooling performance of the developed system was compared to that of a standing column well (SCW) system in a field-scale experiment. Furthermore, the effects of the multi-well pairing system on groundwater levels in the injection well were analyzed by numerical simulation. Moreover, in order to decide the required conditions of the multi-well pairing system, case studies were conducted under various hydraulic conductivity and pumping conditions.